STRATEGI PEMBELAJARAN GURU MATA PELAJARAN FIQIH DALAM MEMOTIVASI PESERTA DIDIK DI MTs DARUN NAJAH KARANGPLOSO MALANG - Indah Nur Malita Sari; Nur Hasan; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Background is based on the case that occurs in students, rejection of the subject of jurisprudence experienced by students, this occurs lack of synchronization of the application of esoteric learning strategies. The application of an appropriate learning strategy can affect the motivation and interest of learners related to student learning outcomes, as well as fiqh learning materials that are easily accepted by students at MTs Darun Najah Karangploso Malang. In this study using the type of qualitative research and the type of descriptive research, which describes a complete description of what is objective according to the data obtained and collected, collecting data conducted by researchers, namely observations, interviews, and research, in the presentation of the results of research interviews using observations and documentation as a reinforcement of data obtained from interviews related to espository learning strategies in motivating students, the research informants are wakakur, fiqh subject teachers, and class VII and VIII students. Keyword : strategy, motivation, fiqih lesson